Performance Evaluation Of Peak-To-Average-Power Ratio Reduction Techniques In OFDM - Al-Heety, Othman S.; Ismail, Mahamod; Zakaria, Zahriladha; Altahrawi, Mohammed A. (International Research Publication House, 2018)
The high demand of using wireless communication leads to establish a new technique of modulation to enhance the throughput of the system and to have a high data rate communication. One of the modern wireless modulation techniques is the Orthogonal Frequency Division multiplexing (OFDM) which considered a suitable technique of modulation in modern wireless application. But there is an important issue to make into consideration when designing OFDM which is the Peak to Average Power Ratio Reduction (PAPR). This study provides a full comparison between using several techniques of PAPR reduction like Clipping and Filtering, Partial Transmit Sequence, DFT Spreading, and Selective Mapping techniques. These techniques are simulated and the PAPR results are obtained for each technique. The comparison between results is also obtained and verified experimentally using MATLAB. The simulation results show that Clipping and filtering technique is the simplest technique of reducing PAPR ratio of the OFDM signal, it depends on the clipping level that satisfies the Signal to Quantization Noise Ratio SQNR. They also show that the partial transmit and selective mapping techniques depends on dividing the OFDM signal into subsignals which the result of transmission these subsignals is nearly to that obtained for the base band signal transmission. The use of Selective Mapping technique (SLM) leads to a PAPR reduction in the simulation from nearly 18 for normal OFDM signal to 12.8 for SLM-OFDM signal. The PAPR ratio from the clipping and filtering technique is 9.5 while the PAPR from SLM is 16.4. The efficiency obtained from the simulation of the SLM technique and clipping and filtering technique are 28.6 and 58.4 respectively.